2015
DOI: 10.1099/jmm.0.000111
|View full text |Cite
|
Sign up to set email alerts
|

A biochemical screening approach to putatively differentiate mammalian pathogenic Oomycota species in the clinical laboratory

Abstract: The report of four novel mammalian pathogenic species of the genus Lagenidium prompted us to study the use of biochemical assays to differentiate the Oomycota mammalian pathogens Pythium insidiosum and Lagenidium spp. We investigated the reaction of 23 Lagenidium and eight Pythium species in various biochemical assays. Because the morphological features of the Oomycota species are similar to those of species in the Entomophthoramycota and Mucormycota, five fungal species with coenocytic hyphae were also includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…A capacity to hydrolyze esculin, but not citrate, lactose and xylose, was the shared biochemical characteristic found in all 26 strains of P. insidiosum ( Table 1 ), consistent with the observations of Vilela, Viswanathan & Mendoza (2015) . The enzymatic components necessary to hydrolyze urea and certain sugars (i.e., dextrose, maltose, sucrose, and trehalose) were found in some strains but were not ubiquitous ( Table 1 ).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…A capacity to hydrolyze esculin, but not citrate, lactose and xylose, was the shared biochemical characteristic found in all 26 strains of P. insidiosum ( Table 1 ), consistent with the observations of Vilela, Viswanathan & Mendoza (2015) . The enzymatic components necessary to hydrolyze urea and certain sugars (i.e., dextrose, maltose, sucrose, and trehalose) were found in some strains but were not ubiquitous ( Table 1 ).…”
Section: Discussionsupporting
confidence: 87%
“…This finding contrasts with reports by Vilela et al, who showed all six P. insidiosum strains tested (including the strains CBS 574.85 and ATCC 28251 of the current study) could utilize urea and these sugars. This is especially important considering maltose and sucrose are two key sugars that were thought to differentiate P. insidosum from other pathogenic oomycetes and fungi ( Vilela, Viswanathan & Mendoza, 2015 ). Failure to breakdown these sugars, in some strains, was markedly associated with slow-growth (growth rate, <5 mm/day) in P. insidiosum ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the difficulty of diagnosing pythiosis and the high costs for laboratory identification of P. insidiosum, as well as the similarity to other agents, especially other oomycetes and filamentous fungi, there is a need for diagnostic tools that can identify rapidly this relevant microorganism. VILELA et al (2015) proposed a biochemical assay for identification of oomycetes; however, this technique should still be used carefully for the evaluation of P. insidiosum isolates (KRAJAEJUN et al, 2018).…”
Section: Introductionmentioning
confidence: 99%